“ELETHIA” AND “A SUDDEN TRIP HOME IN SPRING”: ALICE WALKER’S WOMANIST RESPONSE TO THE ISSUES OF BLACK PEOPLE - Ayyıldız, Nilay Erdem; Kocsoy, F. Gul (My University, 2020)
Alice Walker (1944-) has brought a new dimension to black feminism withher theory of womanism, which she explains in In Search of Our Mothers’Garden (1983). She aims at achieving universality by extending herstruggle to all people around the world, regardless of race, gender, andethnical differences. According to Walker, it requires people toacknowledge their history, matrilineal descent, and black and non-blackauthors’ works inspiring them to struggle. She represents her womanistunderstanding in “Elethia” and “A Sudden Trip Home in Spring” in hercollection entitled You Can’t Keep A Good Woman Down (1981). The titlecharacter of “Elethia” and Sarah in “A Sudden Trip Home in Spring” facetheir problems and realize how to struggle against them. Thus, analyzingWalker’s selected stories, the study indicates that she presents awomanist way out for black people in the racist society through Elethiaand Sarah.
Keywords: Etnik Çalışmalar; Edebiyat; Edebi Teori ve Eleştiri